1991
DOI: 10.1007/bf01691426
|View full text |Cite
|
Sign up to set email alerts
|

Total extracorporeal lung assist—a new clinical approach

Abstract: Total extracorporeal lung assist (ECLA) requires a bypass flow approaching cardiac output. Recirculation of venous blood through the oxygenator is minimized with a veno-right ventricular cannulation technique which separates venous drainage from returned oxygenated blood. A case of posttraumatic ARDS was treated with surface-heparinized veno-right ventricular ECLA for 35 days. Cardiac output was stabilized by means of sedation, hypothermia (35 degrees C) and beta blockers (pulse rate less than 90) in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 18 publications
4
9
0
1
Order By: Relevance
“…A possible explanation for the fact that this RCT could not show benefit from ECMO is that 22 bleeding complications occurred in their LFPPV-ECCO 2 R-treated patients leading to termination of extracorporeal respiratory support in seven patients. Available literature suggests that bleeding complications are frequently related to high-dose heparinization [15,[78][79][80][81][82][83][84]. Heparincoated circuits and membrane oxygenators were used in all of our ECMO-treated patients and we observed a much lower incidence of bleeding complications.…”
Section: Impact Of Ecmo On Survival Ratesmentioning
confidence: 67%
See 2 more Smart Citations
“…A possible explanation for the fact that this RCT could not show benefit from ECMO is that 22 bleeding complications occurred in their LFPPV-ECCO 2 R-treated patients leading to termination of extracorporeal respiratory support in seven patients. Available literature suggests that bleeding complications are frequently related to high-dose heparinization [15,[78][79][80][81][82][83][84]. Heparincoated circuits and membrane oxygenators were used in all of our ECMO-treated patients and we observed a much lower incidence of bleeding complications.…”
Section: Impact Of Ecmo On Survival Ratesmentioning
confidence: 67%
“…The heparin-coated membrane lungs, however, had to be changed frequently due to plasma leakage [85][86][87][88][89], exposing the patient to the risks of such maneuvers. Other authors using ECMO with heparinized equipment have also reported prolonged extracorporeal perfusion times without major bleeding complications [79,80]. Another explanation for the poor survival rates in LFPPV-ECCO 2 R treated patients of Morris et al [25] may be that they applied a mean PIP of 54 cmH 2 O during the entire LFPPV-ECCO 2 R period.…”
Section: Impact Of Ecmo On Survival Ratesmentioning
confidence: 88%
See 1 more Smart Citation
“…The 1979 NHLBI study on extracorporeal membrane oxygenation, performed in patients with very high mortality, did not show a therapeutic benefit of this costextensive technique [81]. Further developments of the concept of extracorporeal gas exchange centered on CO2 elimination (ECCO2-R) or CO2 elimination in combination with partial extracorporeal oxygenation (ECLA) [26,63,134,138]. These techniques, available in a few specialized centers, have been optimized in the past few years, and impressively high survival rates of patients with seriously disturbed gas exchange were presented.…”
Section: Respirator Therapymentioning
confidence: 99%
“…In pigs, at least 25% of the cardiac output must be directed through the pulmonary artery at normothermia to prevent ischemic lung injury (5). If the cardiac output can be directed through the pulmonary artery, total extracorporeal membrane oxygenation (veno-right ventricular ECMO) supplying a patient's whole need for gas exchange, can be run for several weeks without causing lung injury (6)(7)(8). However, total veno-arterial ECMO, bypassing the pulmonary artery circulation, cannot be run for more than a few hours before ischemic injury of the lung vasculature occurs, manifesting itself after weaning from bypass as increased pulmonary vascular resistance or intrapulmonary bleeding (4,5).…”
mentioning
confidence: 99%